The treatment of gender and time in Winterson's and Spark's novels - Radetič, Andreja (Vestnik za tuje jezike, 2009)
Both Jeanette Winterson and Muriel Spark try to challenge and overcome culturally constructed binary oppositions between two genders. Winterson imposes femininity on men and masculinity on women. She denies traditional gender roles. In her novels, men and heterosexuality are marginalized or even overlooked. Both Winterson and Spark portray women, who are active, independent and domineering; they reject marriage, are educated, live on their own and are in control of their lives. The main difference between Winterson's and Spark's women is that the former are heroines and the latter are victims (either of themselves or the others). Both authors deny traditional notion of time and history. Winterson uses history to explore the present. She magnifies the individual's role in history-making and challenges the traditional notion of history being male-constructed. She gives a woman a role in history-making. Both Spark's and Winterson's novels are set anti-linearly with the use of prolepses and antilepses.
Keywords: Winterson, Jeanette, 1959-; Spark, Muriel, 1918-1999; angleški roman; 20.st.; ženski liki; moški liki; književnost; literature; spol; čas; history; zgodovina